Prevalence and associated risk factors of intestinal parasites among sanitation workers and work conditions at Gaza Municipality - Adnan Ibrahim Al Hindi; Fayez M. Shaldoum; Nahla Mezied; Mariam Alreefi (Baghdad Journal of Biochemistry and Applied Biological Sciences)
Background and objective: Sanitation workers (SWs) are a potential source of infection for many intestinal parasites and other enteropathogenic infections as well. The aim of the present study was to determine the prevalence of intestinal parasites carriers among SWs at Gaza Municipality and focusing on the associated risk factors through their work.